PEMBENTUKAN IDENTITAS SOSIAL BUDAYA PADA LORONG BETWEEN TWO GATES DI KAMPUNG PURBAYAN SEBAGAI KAMPUNG PUSAKA DI YOGYAKARTA - Bidayatul Hidayah; Hanum Putri Rahmadewi; Anik Widiastuti (Yayasan Literasi Sains Indonesia, 2026)
This study aims to analyze the formation of socio-cultural identity in the Between Two Gates area in Purbayan Village, a heritage village in Yogyakarta. This study uses a descriptive qualitative approach with a case study method. Data were collected through in-depth interviews, documentation, and literature review, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions with triangulation techniques to ensure data validity. The results show that socio-cultural identity in Purbayan Village is formed through the integration of historical aspects, physical space, and ongoing social practices. The Between Two Gates area serves as a social space that represents the collective identity of the community through traditional settlement patterns, intense social interactions, and the values ​​of harmony and mutual cooperation. Cultural identity is also reflected in the combination of material elements such as traditional house architecture and village landscapes, as well as non-material elements in the form of values, norms, and traditions passed down from generation to generation. This area functions as a living heritage that connects the past with the present through adaptation practices, such as the use of traditional spaces for social activities and cultural tourism.